ON THE INTERACTIONS OF BIRKHOFF GRAVITATIONAL FIELD WITH THE ELECTROMAGNETIC AND PAIR FIELDS - MOSHINSKY, M (UNIVERSIDAD NACIONAL AUTONOMA DE MEXICO, INSTITUTOS DE FISICA Y GEOFÍSICA, CD. MEXICO, DF, MEX, 1952)
The flat space-time theory of gravitation proposed by G. D. Birkhoff is discussed from the standpoint of a field theory and, in particular, the interaction of Birkhoff's field with other fields is developed. This interaction is shown to take place through
PHYS REV LETT
Keywords: INTERACTION, BIRKHOFFS GRAVITATIONAL, ELECTROMAGNETIC, PAIR FIELDS; MULTIDISCIPLINARIA; ELECTROMAGNETISMO; MAGNETISMO